CHALLENGES OF COMMUNITY DEVELOPMENT IN NIGERIA (Journal of Governance and Development (JGD), 2021)
The paper examines the challenges of community development in Nigeria. The lofty goals embedded in community development is being hindered by ravaging poverty and illiteracy, lack of information, economic challenges, social inclusion as well as some cultural factors in the country. Relying on qualitative methods of analysis and second sources of data collection this paper shows that measures such as learning about the community, listening to community members, access to information and issues, developing an action plan and implementing an action plan as well as evaluate results of actions can ensure effective community development in the country. The paper, therefore, concludes that for rapid community development should be considered as crucial to national development. Hence it is necessary to encourage community initiatives for self-determination and development because the federal and the state government cannot adequately provide enough for community needs.